The hebrews: A religious legacy - Carvajal Mena, Ligia (2014)
The first human settlements took place in the river banks such as the Euphrates, Tigris and Nile. Because of their fertility, those lands became the cradle of cultures that left an important legacy for the development of humanity. Within the framework of these cultures is the Hebrew that assuming foreign cultural aspects, reassembled them and made an original break to their culture, especially in the religious area by establishing unequivocally the monotheism, also outstanding buildings combining the religious with the astronomical, as well as the creation of a God with strong ethical background, transcending the national scope to an universal approach.